A fast ship detection algorithm in SAR imagery for wide area ocean surveillance - Xing Xiangwei; Ji Kefeng; Zou Huanxin; Sun Jixiang (2012 IEEE Radar Conference, 2012)
Ship detection is a basic problem to be solved in SAR application of ocean surveillance. To deal with the rapid increasing SAR data, fast algorithm has become a hot topic in the research of ship detection. This paper proposes a fast ship detection algorithm in SAR imagery for wide area ocean surveillance. The algorithm adopts global two-parameter CFAR and adaptive CFAR based K distribution in the coarse and fine detection phase separately. Performances on detection accuracy and efficiency have been analyzed theoretically. Validation results on several space-born SAR images illustrate the fast method can preserve detection accuracy and improve the calculation efficiency.